2011
DOI: 10.1369/0022155411404073
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Bodies in Inflammatory Cells

Abstract: Lipid bodies (LBs), also known as lipid droplets, have increasingly been recognized as functionally active organelles linked to diverse biological functions and human diseases. These organelles are actively formed in vivo within cells from the immune system, such as macrophages, neutrophils, and eosinophils, in response to different inflammatory conditions and are sites for synthesis and storage of inflammatory mediators. In this review, the authors discuss structural and functional aspects of LBs and current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 85 publications
0
112
0
2
Order By: Relevance
“…Quantitative fluorimetric analyses using Nile Red were performed to evalaute a possible accumulation of neutral lipids inside the lipid bodies (LBs). Nile Red is a phenoxazone dye that fluoresces intensely when bound to hydrophobic particles, such as lipid bodies (35). Quantitative fluorimetry indicated that treatments with 1 M POSA or 1 M ITZ were able to induce significant increases in the accumulation of lipid bodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative fluorimetric analyses using Nile Red were performed to evalaute a possible accumulation of neutral lipids inside the lipid bodies (LBs). Nile Red is a phenoxazone dye that fluoresces intensely when bound to hydrophobic particles, such as lipid bodies (35). Quantitative fluorimetry indicated that treatments with 1 M POSA or 1 M ITZ were able to induce significant increases in the accumulation of lipid bodies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In immune cells, such as macrophages, neutrophils, eosinophils, LBs are actively formed in response to inflammatory stimuli and provide a milieu for synthesis and storage of inflammatory mediators (Melo et al, 2011). During pre-implantation embryo development, within the same developmental stage, LBs acquire specific numbers and positioning according to the embryo's state (Kyvelidou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that endocrine inputs relevant to metabolic syndrome and obesity can alter lipid storage in immunocytes. The best-characterized example of this is the accumulation of dietary lipids in foamy macrophages during atherosclerosis, with these lipid droplet pools being sensitive to hormones such as resistin and leptin [12]. Recently we described sensitivity of mast cell lipid body numbers, both in vitro and ex vivo , to insulin, with chronic insulin exposure driving steatosis and marked phenotypic changes in these cells ([13], WEG and HT, manuscript submitted).…”
Section: Introductionmentioning
confidence: 99%